Law, Religion and the Family in Africa: Book Review - Nurul Hidayati (Journal of Islamic Studies and Education, 2024)
The intersection of law, religion, and family structures in Africa presents a dynamic and complex landscape influenced by historical, cultural, and legal pluralism (Green & Kabata, 2021). In Law, Religion and the Family in Africa, M. Christian Green and Faith Kabata provide a comprehensive examination of how these elements interact, sometimes harmoniously and at other times in conflict. This volume, published by African Sun Media, brings together diverse perspectives from scholars across the continent, highlighting key legal, religious, and social challenges that shape family life in Africa.